Forest Cover and Its Management: A Study in Indian Perspective - Pia Ghoshal; Aniruddha Banerji (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 9, 2023)
This article conducts a statewise analysis of the extent of forest cover in India for the past two decades to focus on the level of implementation of various forest conservation policies. India has diverse kinds of forests which offer an enormous potential for crucial ecosystem services, rural economic growth and sustainable development. However, these ecosystems are threatened by deforestation. Moreover, as India has emphasized on the Joint Forest Management (JFM) as a fallout of forest policies after 1988, this article also studies the importance and the current situation of fund allocation of JFM schemes as a potential participation model expected to facilitate better implementation of policies. Our analysis reveals that Indian states have substantial forest cover, some of which has been lost due to various reasons over the past years in some regions. In order to combat such forest cover loss, there is urgent need to enforce steps to sustainably protect forest ecosystems. Along with the governments, the various stakeholders need to be involved in such conservation efforts. The JFM should be encouraged more so that along with better fund allocation there should be efficient use of such funds.